Environmental enrichment mitigates the impact of ancestral stress on motor skill and corticospinal tract plasticity. (6th October 2016) - McCreary, J. Keiko; Erickson, Zachary T.; Metz, Gerlinde A.S.
Highlights: Ancestral stress impaired skilled walking abilities in rats. Ancestral stress reduced axonal density of corticospinal projections. Enriched environment mitigated adverse consequences of ancestral stress in the motor system. Abstract: Background: An adverse fetal environment in utero has been associated with long-term alterations in brain structure and function, and a higher risk of neurological disorders in later life. A common consequence of early adverse experience is impaired motor system function. A causal relationship for stress-associated impairments and a suitable therapy, however, have not been determined yet. Objective: To investigate the impact of ancestral stress on corticospinal tract (CST) morphology and fine motor performance in rats, and to determine if adverse programming by ancestral stress can be mitigated by environmental enrichment therapy in rats. Methods: The study examined F3 offspring generated by three lineages; one with prenatal stress only in the F1 generation, one with compounding effects of multigenerational prenatal stress, and a non-stress control lineage. F3 offspring from each lineage were injected with biotinylated dextran amine (BDA) into the motor cortex for anterograde tracing of the CST. Results: Examination of the CST revealed reduced axonal density in the ancestrally stressed lineages. These anatomical changes were associated with significant impairments in skilled walking, as indicated by reduced foot placement accuracy and disturbed inter-limb coordination. Therapeutic intervention by environmental enrichment reduced the neuromorphological consequences of ancestral stress and restored skilled walking ability. Conclusions: The data suggest a causal relationship between stress-induced abnormal CST function and loss of fine motor performance. Thus, ancestral stress may be a determinant of motor system development and motor skill. Environmental enrichment may represent an effective intervention for the adverse programming by ancestral stress and trauma.